Molecular docking study of naturally derived flavonoids with antiapoptotic BCL-2 and BCL-XL proteins toward ovarian cancer treatment - Ghani M.F.A.; Othman R.; Nordin N. (Wolters Kluwer Medknow Publications, 2024)
Indexed by Scopus/ERA